1993
DOI: 10.1007/bf00010763
|View full text |Cite
|
Sign up to set email alerts
|

Sources of N uptake by wheat (Triticum aestivum L.) and N transformations in soil treated with a nitrification inhibitor (nitrapyrin)

Abstract: Rates of N uptake by spring wheat as ammonium and as nitrate, and rates of nitrification, gross N immobilization and gross N mineralization were measured in a pot experiment during 84 days of growth in a clay soil. Soil treatments included an unfertilized control and addition of 15NH4NO 3 or NHn~SNO3 in the absence and presence of N-serve 24E.Incorporation of ammonium into the soil organic N pool was considerably higher in the presence compared to the absence of nitrapyrin, but the processes contributing to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The yield in this study was lower than reported earlier [ 13 , 41 42 ]. Our findings were more similar to the report by Crawford and Chalk [ 43 ] who found that there was no significant difference in yield between fertilizer N plus nitrapyrin and N applied only. Under the tested condition of drip-irrigated plot with input of 225 kg N ha -1 , the relatively high NUE (>50%) was gained, and more importantly, nitrapyrin addition increased NUE by 10.7% ( P <0.05).…”
Section: Resultssupporting
confidence: 91%
“…The yield in this study was lower than reported earlier [ 13 , 41 42 ]. Our findings were more similar to the report by Crawford and Chalk [ 43 ] who found that there was no significant difference in yield between fertilizer N plus nitrapyrin and N applied only. Under the tested condition of drip-irrigated plot with input of 225 kg N ha -1 , the relatively high NUE (>50%) was gained, and more importantly, nitrapyrin addition increased NUE by 10.7% ( P <0.05).…”
Section: Resultssupporting
confidence: 91%
“…There was no effect on the rate of NH 4 + immobilization after inhibitor addition (Fig. 1), although the inhibitors blocked transformation of NH 4 + to NO 3 − supporting previous reports by Chalk (1990) and Crawford and Chalk (1993). In our study, soil pH might be a key factor influencing the effectiveness of DMPP and C 2 H 2 on nitrification; however, their effectiveness might also have been affected by other soil properties such as soil texture .…”
Section: Discussionsupporting
confidence: 81%
“…Over a period of 20 days it was estimated that 61% of plant N was taken up as NH 4 + . Crawford and Chalk (1993) found that the uptake of NH 4 + by wheat (U 1 ) during 0 to 20 days in a clay soil with high biological activity was less, both in absolute amounts and relative proportions, than the uptake of NO 3 − (U 2 + U 3 ) in paired pots, but when the nitrification inhibitor nitrapyrin was added with the fertilizer, uptake of NH 4 + increased and NO 3 − decreased, so that the relative proportions taken up by wheat were approximately equal. On the other hand, application of nitrapyrin to a pasture soil had little effect on the proportional uptake of NH 4 + and NO 3 − by perennial ryegrass, because the soil had a low nitrification capacity (Geens et al, 1991).…”
Section: Hydroponic Studiesmentioning
confidence: 99%
“…It is also possible to estimate U 2 from the data of Crawford and Chalk (1993) by using the difference in the uptake of N in ± inhibitor treatments. For example, U 2 = U n(−inhibitor) -U n(+inhibitor) = 50-31 = 19 mg N kg −1 soil.…”
Section: Hydroponic Studiesmentioning
confidence: 99%